Commodification of Religion in Marketing Communication for Sharia-Compliant Properties - Darojatun, Rina; Busro, Busro (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2024)
This study explores the influence of integrating religious values and the use of religious symbols in marketing Sharia-compliant properties on consumer purchase decisions. Employing a netnographic method, this analysis observes consumer interactions on the Instagram account @shariagreenland, revealing how spiritual resonance and the commodification of religious symbols affect consumer preferences and behavior in the property sector. The findings reveal that religious symbols are strategically used in the marketing of Sharia-compliant properties, not only to support religious identity but also as a tool to create added value in consumer perception. These symbols are integrated into various marketing aspects, from property branding using the term “Islamic Housing”, to payment systems and facilities that comply with Islamic law, indicating the occurrence of religious commodification. Furthermore, this research identifies marketing strategies that commodify religious symbols as a major differentiating factor influencing consumer interest. The results of this study provide important insights for property developers in formulating effective marketing strategies, emphasizing the need for an authentic and transparent approach in integrating religious values into their product offerings. These findings contribute to the literature on consumer behavior in the context of Sharia-compliant properties and highlight broader social and cultural dynamics surrounding the commodification of religion in contemporary marketing.